Endometriosis and ovarian cancer - what they have in common? - Natalia Zarankiewicz; Katarzyna Kosz; Aleksandra Kuchnicka; Martyna Zielińska; Natalia Wolanin; Bogumiła Ciseł (Kazimierz Wielki University, 2020)
Introduction and purpose: Endometriosis is one of the most common diseases among women in the reproductive age. Although its etiology remains not fully understood, several models of endometriosis development are taken into consideration. Many studies have been focused on hormonal and genetic alterations in endometriosis. The results of these studies allow for a thesis on common origin of endometriosis anda few types of ovarian cancer. The aim of this review is to present actual knowledge about endometriosis' development conditions and a possible association with ovarian cancer. Material and method: The review concerned articles published in years 2012-2020, which were collected in the PubMed and Google Scholar. Particular attention was paid to the development of both the endometriosis and Endometriosis-Related Ovarian Neoplasms (ERONs) and their genetic disorders. Results: Endometriosis development is connected with several risk factors and also immune, hormonal and genetic alterations. Some authors postulated that malignant transformation of endometriosis may be a multi-step process powered by increasing levels of estrogen. Many studies confirmed that mutations of ARID1A and PIK3CA genes are likely to be present in the majority of cases of ovarian cancer with adjacent endometriosis. Conclusions: The awareness of clinical features and medical complications of endometriosis is spreading increasingly around the world. Many studies are focused on genetic causes of this illness. It may be supposed that we will be able to select women with endometriosis and increased risk of ovarian cancer and prevent its development.